Budgeting and Financing of Higher Education - Jailani Syahputra Siregar; Rahmat Hidayat Rambe; Refi Syahputra; Baginda Baginda; Mesiono Mesiono (Universitas Muhammadiyah Enrekang, 2022)
The increase in people's interest in continuing their studies at universities is now starting to improve. Higher Education statistical data for 2020 shows only a 0.01 percent decrease from the previous year. However, the quality of publications and funding as well as postal funding for each Indonesian tertiary institution is still far from expectations. Therefore, it is necessary to have harmony and collaboration between various parties in improving these weaknesses, both the government sector, educators (lecturers) and the beneficiaries of education itself. The method used in finding the results of this research is literature study with descriptive analysis techniques. Some of the findings discussed in this study, in relation to increasing the effectiveness and efficiency of higher education budgeting and financing, include; 1) Administrative, is an analytical study that is very important so that financial managers consisting of planning, organizing, directing and evaluating, can become a barometer, reliability and financial accountability in terms of effective and efficient administration. 2) The budget structure is also the focus of analysis for policy makers at the tertiary level, in order to make it easier to prepare the budget by grouping job descriptions in budgeting into the easiest offer, namely making enstra (strategic plans). 3) The budgeting process, in this case, the leadership's ability to manage complexes by understanding the needs of the departments (prodi) and other sub-sections. Hence providing fair opportunities for subordinates. Participation in the drafting process in all sectors (sub-sections) in tertiary institutions. 4) Education, government and community relations. An analysis of the collaboration of the three sectors is a necessity, so that inputs, outputs and outcomes can be realized by understanding and implementing educational, cultural and institutional relations.